Studies in Natural Products Chemistry - Bioactive Natural Products. (Pt. M) vol. 33 - Rahman, Atta-ur 1942- (San Diego : Elsevier Science [Imprint], 2006)
Annotation Natural products present in the plant and animal kingdom offer a huge diversity of chemical structures which are the result of biosynthetic processes that have been modulated over the millennia through genetic effects. With the rapid developments in spectroscopic techniques and accompanying advances in high-throughput screening techniques, it has become possible to isolate, determine the structures and biological activity of natural products rapidly, thus opening up exciting new opportunities in the field of new drug development to the pharmaceutical industry.The present volume contains 22 articles written by leading experts in natural product chemistry on biologically active natural products. It includes research on a variety of different classes of natural products including sesquiterpenes, quassinoids, diterpenoids, lignans, oligostilbenes, phenylethanoids, phenylpropanoid glycosides, curcumin analogues, glycosphingolipids etc. Many of these have been found to be active in a number of different disease conditions.* Timely reviews written by international authorities in the field* Topics ranging from purely chemical to very biological* The 13th volume in the series to be devoted to bioactive natural products
Includes index.
Scholarly & Professional